Associations between BRAF(V600E) and prognostic factors and poor outcomes in papillary thyroid carcinoma: a meta-analysis - Liu, Chunping; Chen, Tianwen; Liu, Zeming (World journal of surgical oncology, 2016)
The objective of this study is to perform a meta-analysis to evaluate the associations between the BRAF(V600E) mutation status and aggressive clinicopathological features and poor prognostic factors in papillary thyroid cancer. A literature search was performed within the PubMed, MEDLINE, Web of Science databases, and EMBASE databases using the Medical Subject Headings and keywords from January 2003 to July 2015. Individual study-specific odds ratios and confidence intervals were calculated, as were the Mantel-Haenszel pooled odds ratios for the combined studies. Sixty-three studies of 20,764 patients were included in the final analysis. Compared with wild-type BRAF, the BRAF(V600E) mutation was associated with aggressive clinicopathological factors, including extrathyroidal extension, higher TNM stage, lymph node metastasis, and recurrence, and was associated with reduced overall survival; however, there was no significant association between the presence of BRAF mutation and distant metastasis. BRAF mutations are closely associated with aggressive clinicopathological characteristics and poorer prognosis in papillary thyroid cancer. Accordingly, aggressive treatment should be considered for papillary thyroid cancer patients with BRAF mutation.